Impact of Bio-Adhesive Addition on the Properties of Cement Bricks Incorporating Quarry Dust and Kenaf Core - Faizol Kamar, Nurul Atika; Lokman Hakim Ismail; Khairol Kamaruddin (Recent Trends in Civil Engineering and Built Environment, 2025)
In the context of sustainability issues arising from the disposal of waste materials like quarry dust and agricultural residues such as kenaf core, there is an important need to discover alternative materials and additives for enhancing the properties of cement-based products. The purpose of this study is to assess the effect of integrating bio-adhesive into cement bricks, including those containing quarry dust and kenaf core. The evaluation was to compare cement bricks’ water absorption properties and compressive strength with and without bio-adhesive. The study used the volume approach in mix proportions (M1 to M6), considering weight proportions and ratios of kenaf core, quarry dust, and bio-adhesive. A total of 54 samples were produced. Tests included specific gravity test, sieve analysis, water absorption, hardened density, and compressive strength test to evaluate the cement bricks. According to the study, substituting kenaf core with quarry dust should not exceed 25% in order to satisfy the specified compressive strength of 5.2 Mpa. Water absorption increases as the proportion of the kenaf core increases. The use of more than 25% kenaf core lowers the brick density. Furthermore, bio-adhesive strengthens the contact between cement and fibers, increasing strength performance and decreasing brittleness. These discoveries pave the path for eco-friendly building materials that are in line with SDG 9.